PERBANDINGAN PENGARUH MODEL CO-OP CO-OP DENGAN INTEGRATED READING AND COMPOSITION TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 PAGARALAM - Yuspitra Aliati; Ikbal Barlian; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
The title of this research is “The Comparison of the Influence between Co-op Co-op Model and Integrated Reading and Composition Model in Learning Outcomes in Economics Subject in SMA Negeri 1 Pagaralam. For the research question in this study is “Whether or not there was any significant different influence in learning outcomes in learning Economics who were taught by using Co-op Co-op Model and those who were taught by using Integrated Reading Composition Model in SMA Negeri 1 Pagaralam.” This study is a comparative research which is used completely randomized design and pretest posttest. The populations of this study are tenth grade students of SMA Negeri 1 Pagaralam. The writer applied cluster random sampling, XH were chosen as experimental 1 class and XI class were chosen as experimental 2 class. Each of them consists of 34 students. For collecting the data, the writer used tests and observation. The hypothesis used parametric statistics, one way ANOVA and Fhitung value is bigger than Ftable so H0 is rejected and H1 is accepted. The result showed there was a significant different influence in learning outcomes in learning Economics who were taught by using Co-op Co-op Model and those who were taught by using Integrated Reading Composition Model in SMA Negeri 1 Pagaralam.” According to the difficulties in this study, for the teacher who will apply Co-op Co-p Model should offer the material in a good way and guide the students who find difficulties in learning the material individually. The teacher also controls the students when learning the material so there is no student who counting another friend in their groups. For the teacher who will apply Cooperative Integrated Reading and Composition Model should deliver the relevant texts and teach the material in easy way to be understood by the students.